Further electron microscopic studies on the expression of Escherichia coli group II capsules. - Kröncke, K D (1990)
The de novo expression of Escherichia coli K1, K5, and K12 capsules was analyzed with immunoelectron microscopy in temperature upshift experiments, with upshift from 18 degrees C (capsule restrictive) to 37 degrees C (capsule permissive). Newly produced capsular polysaccharides appeared at the cell surface atop membrane adhesion sites (Bayer's junctions). After plasmolysis of the bacteria at an early expression stage, the capsular polysaccharides were labeled at discrete sites in the periplasm by the immunogold technique. After temperature upshift in the presence of carbonyl cyanide m-chlorophenylhydrazone (CCCP) or chloramphenicol, the polysaccharides were labeled in the cytoplasm.